Flexible touchpad via LIG: preliminary result - Seow, Jerrell (Nanyang Technological University, 2023)
Wearable technologies are wearable gadgets that may be used as body implants, embedded in garments, tattooed on the skin, or most commonly worn as accessories. The demand for this technology is emerging expeditiously and becoming one of the most popular technologies in recent years because of the many applications it offers.